Present value of firm asset in case of correlated defaults: a generalized structural approach of credit risk - Valužis, Mantas (Lietuvos matematikos rinkinys, 2007)
This article investigatesthe present value of a firm’s asset in the case of n ≥ 2 correlateddefaults. The structural approach of credit risk is developed in the case when default boundaries follow geometric Brownian motions. Correlated defaults are defined by the implied correlation of Brownian motions. The operational risk and the risk of financial market changes are allowed in this model. Also, the impact of implied correlation to the present value of firm’s asset is shown numerically.
Keywords: correlated defaults; implied correlation; present value